INSTRUMEN KEBIJAKAN MAKROEKONOMI DALAM MEMPENGARUHI OUTPUT: SUATU ANALISIS APLIKASI ST. LOUIS EQUATION DI INDONESIA - Yunisvita Yunisvita (Jurnal Ekonomi Pembangunan, 2013)
One of the indicator that measures the ability of a country is output , therefore, to increase and  to stabilize the output for countries that have a mixed system, which  is the government plays an important role in  economy . Government has a role to make policy called macroeconomic policy , macroeconomic policy is divided into two: monetary policy and fiscal policy . Nowadays there are differences opinion between the monetarists and the fiscalist wherein each theorists believe that the policies  they believe  is more effective in increasing output. The purpose of this study is to see which policy is more effective in  Indonesia with St.Louis Equation applicatioan. Data used is the money supply ( M2 ) as a tool of monetary policy , government spending ( G ) as a tool of fiscal policy , and the Gross Domestic Product ( GDP ) as a measure of output . The analytical method used is using ordinary least square method and produce a good estimation results with the classical assumption . The result shows that the monetary and fiscal policy are significant and positive affect output , the effect of fiscal policy is more effective in the long term in Indonesia. Model estimation does not contravene the classic assumption except autocorrelation and can be overcome by transforming the model by using the scheme AR ( 1 ) . Keywords : Macroeconomic Policy, M2, G, Output, St .Louis Equation